ANALISIS SIFAT KIMIA TANAH PADA BEBERAPA PENGGUNAAN LAHAN DI KECAMATAN BATUI SELATAN - Djamaluddin, Ismail; Sataral, Mihwan; Manggo, Andi Liany (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2025)
Soil chemical analysis is the measurement and evaluation of the chemical components present in soil. This study aims to examine the effect of differences in land use on soil chemical properties. This research was conducted from May to July 2024 in South Batui District. Soil sampling locations were based on land use, namely food crops, horticulture, and plantations. The data used in this study were analyzed through laboratory analysis and then processed using Microsoft Excel 2013. The results of this study are that the chemical properties of the soil in several land uses in Batui Selatan District have a significant effect on several soil chemical properties including C-organic and N-total. Meanwhile, for other soil chemical properties pH, P2O5, K-Total, CEC and KB do not have a significant effect on the use of chili, corn and cocoa land. This is influenced by different land management in each land use. Land use in Batui Selatan District is not optimal, because farmers do not clearly understand the needs of plants in each location. To increase soil fertility in various types of land uses, there are several ways that can be done including the addition of organic materials, the use of appropriate fertilizers (both organic and inorganic), proper soil processing, improvement of drainage and irrigation systems, and the application of diverse planting patterns (crop rotation).